Evolution of the technological, sensory, and nutritional quality of gluten-free cookies: a critical review - MELO, Bruna Guedes de (2023)
Understanding the scenario of the development of gluten-free products, the relationship with the public, and the present challenges is of paramount importance to advance the development of these products successfully. This review focuses on gluten-free cookies, with a discussion of the main results found for the different types of raw materials and their influence on product quality and the lack of innovation in new processes for such products. According to the presentation of the studies, the main challenges for the development of gluten-free cookies are the repetition of starchy raw materials and the processes that lead to technological and sensory results that displease consumers because they are being compared with the affective memory of the gluten-free product, which unbalanced the nutritional value of the products because they have high levels of carbohydrates and fat. In the food industry, innovations and changes are already occurring, such as the use of protein and fiber raw materials. However, it is still necessary to develop strategies dissociated from those used for gluten-free baked goods that are more personalized for this market, which, compared with wheat products with more than 2000 years of history, is in the first steps of development.